Platelet activation and anti-phospholipid antibodies collaborate in the activation of the complement system on platelets in systemic lupus erythematosus. - Christian Lood (Public Library of Science (PLoS), 2014)
Anti-phospholipid (aPL) antibodies are important contributors to development of thrombosis in patients with the autoimmune rheumatic disease systemic lupus erythematosus (SLE). The underlying mechanism of aPL antibody-mediated thrombosis is not fully understood but existing data suggest that platelets and the complement system are key components. Complement activation on platelets is seen in SLE patients, especially in patients with aPL antibodies, and has been related to venous thrombosis and stroke. The aim of this study was to investigate if aPL antibodies could support classical pathway activation on platelets in vitro as well as in SLE patients. Furthermore, we investigated if complement deposition on platelets was associated with vascular events, either arterial or venous, when the data had been adjusted for traditional cardiovascular risk factors. Finally, we analyzed if platelet complement deposition, both C1q and C4d, was specific for SLE. We found that aPL antibodies supported C4d deposition on platelets in vitro as well as in SLE patients (p = 0.001 and p<0.05, respectively). Complement deposition on platelets was increased in SLE patients when compared with healthy individuals (p<0.0001). However, high levels of C4d deposition and a pronounced C1q deposition were also seen in patients with rheumatoid arthritis and systemic sclerosis. In SLE, C4d deposition on platelets was associated with platelet activation, complement consumption, disease activity and venous (OR = 5.3, p = 0.02), but not arterial, thrombosis, observations which were independent of traditional cardiovascular risk factors. In conclusion, several mechanisms operate in SLE to amplify platelet complement deposition, of which aPL antibodies and platelet activation were identified as important contributors in this investigation. Complement deposition on platelets was identified as a marker of venous, but not arterial thrombosis, in SLE patients independently of traditional risk factors and aPL antibodies. Further studies are needed to elucidate the role of complement deposition on platelets in development of venous thrombosis.